2008
DOI: 10.1152/ajpendo.90440.2008
|View full text |Cite
|
Sign up to set email alerts
|

Pax6 and Pdx1 are required for production of glucose-dependent insulinotropic polypeptide in proglucagon-expressing L cells

Abstract: cose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1) are incretin hormones that play important roles in maintaining glucose homeostasis and are being actively pursued as novel therapeutic agents for diabetes. GIP is produced by dispersed enteroendocrine cells and interestingly at times is coexpressed with GLP-1. We sought to determine the factors that selectively define GIP-vs. GLP-1-expressing cells. We performed comparative immunostaining of Pax6 and Pdx1 in GIP-and GLP-1-secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 43 publications
5
51
1
Order By: Relevance
“…It has been proposed that Pdx-1 and Pax6 are required for GIP expression (Offield et al, 1996;Jepeal et al, 2005;Fujita et al, 2008) while Pax6 has been reported to activate the expression of the glucagon gene (Hill et al, 1999). At e-17, ileum of embryos contain GIPþPdx-1þ ( Fig.…”
Section: The Majority Of L Cells Of Embryos Coexpress Gipmentioning
confidence: 95%
See 2 more Smart Citations
“…It has been proposed that Pdx-1 and Pax6 are required for GIP expression (Offield et al, 1996;Jepeal et al, 2005;Fujita et al, 2008) while Pax6 has been reported to activate the expression of the glucagon gene (Hill et al, 1999). At e-17, ileum of embryos contain GIPþPdx-1þ ( Fig.…”
Section: The Majority Of L Cells Of Embryos Coexpress Gipmentioning
confidence: 95%
“…GIP and GLP-1 are termed incretins because they stimulate insulin secretion from pancreatic beta-cells following nutrient ingestion (Baggio and Drucker, 2007). While the primary site of endogenous GIP release is the endocrine K cell of the duodenum and proximal jejunum, several reports indicate the presence of LK cells in adult mouse ileum (Mortensen et al, 2003;Fujita et al, 2008;Grigoryan et al, 2012).…”
Section: Developmental Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the presence of Pdx1 determines whether gastrointestinal L-cells will co-express GIP. 163 Most Nkx6.1-expressing cells also express serotonin, and some express gastrin. Nkx6.1 is not expressed in Pdx1-deficient mice, indicating that Pdx1 acts upstream of Nkx6.1 in enteroendocrine differentiation.…”
Section: Cell Differentiation and Intestinal Adaptationmentioning
confidence: 99%
“…In mice, PAX6 is needed for the differentiation of gastric inhibitory peptide (GIP) and glucagon-like peptide (GLP)-1-and GLP-2-producing cells in the intestine [8]. Furthermore, PAX6 regulates the production of GIP and proglucagon [9] as well as the main enzymes involved in GIP, proinsulin and proglucagon processing: PC2 and PC1/3 [2,[10][11][12][13]. PAX6 could thus affect incretin levels either by changing the expression of the propeptide genes or the levels of processing enzymes.…”
Section: Introductionmentioning
confidence: 99%